2020
DOI: 10.3347/kjp.2020.58.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characteristics of Anisakis typica Larvae in Two Species of Threadfin Bream, Nemipterus hexodon and N. japonicus, from the Gulf of Thailand

Abstract: The third stage larvae (L3) of <i>Anisakis typica</i> were detected in 2 species of threadfin bream, <i>Nemipterus hexodon</i> and <i>N. japonicus</i>, from the Gulf of Thailand, and were morphologically and molecularly characterized. Total 100 threadfin breams, 50 <i>Nemipterus hexodon</i> and 50 <i>N. japonicus</i>, were examined with naked eyes after the opening of abdominal cavity with scissors. Almost all infected larvae remained alive and active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 28 publications
4
23
2
Order By: Relevance
“…Vietnamese A. typica were genetically close to those from China, Thailand, Indonesia, Papua New Guinea, and Australia, to make a common group that was separated from another group of America, Brazil, Turkey, and Portugal. Our analysis is in agreement with a previous report that the separation of A. typica populations related to geographical origins ( Tunya et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Vietnamese A. typica were genetically close to those from China, Thailand, Indonesia, Papua New Guinea, and Australia, to make a common group that was separated from another group of America, Brazil, Turkey, and Portugal. Our analysis is in agreement with a previous report that the separation of A. typica populations related to geographical origins ( Tunya et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
“…However, recent studies based on morphological and molecular approaches provided descriptions and microphotographs showing differences between L3 larvae of A. pegreffii and A. typica ( Chen and Shih, 2015 ; Sonko et al, 2019 ). In addition, Tunya et al (2020) suggested that the protruded mucron of L3 larvae can be used to identify anisakid larvae at the species level: the protruded mucron of A. simplex was cone-shape, while that of A. typica was cylindrical-shape, which is narrower and longer than that of A. simplex . According to these, L3 larvae of Anisakis specimens found in this study were identified as A. typica .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations